2016
DOI: 10.1007/s11743-016-1894-8
|View full text |Cite
|
Sign up to set email alerts
|

Coagel Prepared from Aqueous Octyl β‐d‐Galactoside Solution

Abstract: Structuring of semi-crystalline networks in water systems is significant for a variety of industrial applications. In the present work, we investigated the coagel formation from aqueous octyl b-D-galactoside (C 8 -b-Gal) solutions and characterized the crystal structure and crystallite network in the prepared coagel. Differential scanning calorimetry (DSC) confirmed that the Krafft boundary temperature (T K ) is 32-35°C for C 8 -b-Gal concentrations below 30 wt% and a knee of the Krafft boundary exists around … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 33 publications
1
7
1
Order By: Relevance
“…As shown in the figure, all of the surface regions consisted of polycrystalline species with sub-micrometric to micrometric scale lengths. In previous studies, the MOβGal tended to form fiber structures, not only in aqueous solutions, but also on solid surfaces when the solution was drop-casted on the Si substrate [29]. However, in this study, no fiber structure was discernible, indicating that the film consisted of rapidly formed polycrystallites without sufficient time to grow one-dimensionally on the substrate.…”
Section: Moβgal Polycrystalline Films With Different Thicknessescontrasting
confidence: 60%
“…As shown in the figure, all of the surface regions consisted of polycrystalline species with sub-micrometric to micrometric scale lengths. In previous studies, the MOβGal tended to form fiber structures, not only in aqueous solutions, but also on solid surfaces when the solution was drop-casted on the Si substrate [29]. However, in this study, no fiber structure was discernible, indicating that the film consisted of rapidly formed polycrystallites without sufficient time to grow one-dimensionally on the substrate.…”
Section: Moβgal Polycrystalline Films With Different Thicknessescontrasting
confidence: 60%
“…In a preliminary study, the addition of NaCl was confirmed to prolong the stability of the sol state of an Oct-Gal-water system at 4 . Although rapid precipitation within 1 min has been observed in the absence of NaCl 33 , it can be inhibited for at least 35 min in the presence of a 1.0 M NaCl aqueous solution under the same conditions. Such elongation of the induction period for the precipitation of the Oct-Gal crystal was expected to be crucial to prevent rapid precipitation during cooling.…”
Section: Effect Of Electrolyte Addition On the Physicochemicalmentioning
confidence: 90%
“…Oct-Gal was prepared in a manner similar to the method reported previously by our group 33 and used after drying under vacuum at 60 for 2 h. Water and electrolytes purchased from Wako Pure Chemical Industries Ltd. were used as received. The sample solutions were prepared by the dissolution of prescribed amounts of Oct-Gal and electrolyte in water at a bath temperature of 50 .…”
Section: Experimental Procedures 21 Materialsmentioning
confidence: 99%
See 2 more Smart Citations